Predicting hemorrhagic transformation in patients not submitted to reperfusion therapies - Andrade, Joao Brainer Clares de; Mohr, Jay P.; Lima, Fabricio Oliveira; Carvalho, Joao Jose de Freitas; Farias, Victor Aguiar Evangelista de; Oliveira-Filho, Jamary; Pontes-Neto, Octavio Marques; Bazan, Rodrigo [UNESP]; Merida, Kristel Larisa Back; Franciscato, Luisa; Pires, Matheus Mendes; Modolo, Gabriel Pinheiro [UNESP]; et al. (Elsevier B.V., 2020)
Background: Well studied in patients with ischemic stroke after reperfusion thera-pies (RT), hemorrhagic transformation (HT) is also common in patients not treated with RT and can lead to disability even in initially asymptomatic cases. The best predictors of HT in patients not treated with RT are not well established. Therefore, we aimed to identify predictors of HT in patients not submitted to RT and create a user-friendly predictive score (PROpHET). Material and Methods: Patients admitted to a Comprehensive Stroke Center from 2015 to 2017 were prospectively evaluated and randomly selected to the derivation cohort. A multivariable logistic regression modeling was built to produce a predictive grading score for HT. The external vali-dation was assessed using datasets from 7 Comprehensive Stroke Centers using the area under the receiver operating characteristic curve (AUROC). Results: In the derivation group, 448 patients were included in the final analysis. The validation group included 2,683 patients. The score derived from significant predictors of HT in the multivariate logistic regression analysis was male sex (1 point), ASPECTS <= 7 (2 points), presence of leukoaraiosis (1 point), hyperdense cerebral middle artery sign (1 point), glycemia at admission >= 180 mg/dL (1 point), cardioembolism (1 point) and lacunar syndrome (-3 points) as a protective factor. The grading score ranges from -3 to 7. A Score >= 3 had 78.2% sensitivity and 75% specificity, and AUROC of 0.82 for all cases of HT. In the validation cohort, our score had an AUROC of 0.83. Conclusions: The PROpHET is a simple, quick, cost-free, and easy-to-perform tool that allows risk stratification of HT in patients not submitted to RT. A cost-free computerized version of our score is available online with a user-friendly interface.
Keywords: Ischemic stroke; Hemorrhagic transformation; ComplicationVascular neurology